Campbell's operative orthopaedics - Azar, Frederick M.; Beaty, James H.; Canale, S. Terry; Campbell, Willis C. (Willis Cohoon), 1880-1941. (Philadelphia, PA : Elsevier, Inc., 2021)
Campbell's Operative Orthopaedics, 14th Edition is a comprehensive and authoritative guide covering the latest techniques, advancements, and best practices in orthopedic surgery. This edition includes in-depth, step-by-step instructions for thousands of surgical procedures across all orthopedic subspecialties, including trauma, pediatrics, oncology, and spine surgery. Each chapter is enhanced with detailed illustrations and full-color intraoperative photographs to clarify complex concepts and assist surgeons in mastering essential skills. Updated content highlights the latest minimally invasive approaches, new implant options, and evolving standards of care, making it an invaluable resource for orthopedic surgeons, residents, and healthcare professionals involved in musculoskeletal care.
Includes bibliographical references and index.
Keywords: Orthopedic surgery